The Effectiveness of Genially-Based Interactive Media in Improving Fourth-Grade Elementary School Students’ Understanding of Photosynthesis - Putri Rahmawati; Nury Yuniasih; Aris Sri Sunarti (Universitas Negeri Surabaya, 2026)
This classroom action research aims to determine the effectiveness of Genially-based interactive media in improving fourth-grade elementary school students’ conceptual understanding of photosynthesis. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection was conducted through achievement tests. Data analysis utilized the N-Gain calculation to determine improvements in students’ conceptual understanding. The results indicate that the use of Genially media effectively enhances students’ conceptual understanding. In Cycle I, the low N-Gain category accounted for 42.86%, the moderate category for 57.14%, and no students fell into the high category. In Cycle II, there was an improvement: the moderate category increased to 47.63% and the high category to 52.38%, while the low category was no longer present. These results indicate that Genially-based interactive media is effective for teaching photosynthesis in science education because it enhances student engagement and conceptual understanding more effectively